CONTROLE QUÃMICO DAS DOENÇAS FOLIARES DO AMENDOIM (Arachis hypogaea L.) - Lopes, Maria Elizabete B. M.; Lasca, Dalmo H. C.; Guilhem, Dulcinei J.; Montes, Sônia M. N. M.; Cesário, Antonio C.; Ceravolo, Leonardo (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DAS DOENÇAS FOLIARES DO AMENDOIM (Arachis hypogaea L.)